Mobile Alcohol Biosensors and Pharmacotherapy Development Research - Roberts, Walter (Alcohol, 2018)
Recent advances in biosensor technology herald a major shift in how alcohol use will be tracked in humans. Wearable biosensors can passively and continuously monitor wearers’ alcohol consumption in real time. An important application of these biosensors is to improve how medication for alcohol use disorder (AUD) is tested in clinical research. Both laboratory-based screening paradigms and clinical trials have methodological problems that impact their efficiency and predictive validity. Medication screening using laboratory-based methods is a resource intensive assessment of a single episode of behavior in a non-representative setting. Clinical trials rely on participant self-report to document medication-induced changes in drinking behavior. This review describes how mobile biosensors can be leveraged to improve AUD medication development research. We first review the current state of alcohol biosensor technology with a focus on strengths and limitations of the devices. We describe how multiple biosensors can be combined to create a far more detailed record of drinking compared to single biosensor platforms. We then discuss each phase of the medication development pipeline in turn (i.e., Phases 1 – 4) and describe how mobile biosensors can be incorporated in standard medication testing paradigms to improve efficiency and predictive validity. We conclude with discussion of challenges associated with using currently available biosensors for medication testing and recommendations for researchers wishing to incorporate alcohol biosensors into their own research.